A Review on Covid-19 effect in Malaysia’s Tourism Industry - Nur Afrina Aida Binti Mohd Azmi; Azrul Azim Mohd Yunus; Arif Asraf Mohd Yunus (Penerbit USIM, Universiti Sains Islam Malaysia, 2024)
E-Proceeding Kolokium Siswazah Fakulti Sains Dan Teknologi 2020 (KOSIST 2020) “Synergizing Innovation and Research Through Science and Technology” 9th December 2020 Organized by Faculty Science and Technology